Endophyte Initiation Beauveria bassiana (Balsamo) Vullemin (Hypocreales: Cordycipitaceae) in Reduction of Aphis glycine Matsumura (Hemiptera: Aphididae) Investation in Soybean (Glycine max (L.) Merrill) Plant - Mufidah Afiyanti; Rina Rachmawati; Achmad Faisal Akbar; Rose Novita Sari Handoko; Bambang Tri Rahardjo (Indonesian Journal of Environment and Sustainable Development, 2019)
Soybean (Glycine max (L.) Merrill) is a universal important plant. Its production has decreased each year. A major problems is a pest known as Aphis glycine Matsumura (Hemiptera: Aphididae) which caused the decline of yield up to 40%. Thus, there is a need to control A. glycine. Recent studies showed B. bassiana has a potency as endophyte in Vicia faba (Fabaceae) plant tissue. It could harm A. gossypii and causes death up to 57,7%. Therefore, the aim of this research is to control infestation of A. glycine by using B. bassiana. This research used Randomized Block Design with soybean plant Anjasmoro variety as samples. The initiation of B. bassiana was conducted by using seed-soaking and soil-wetting methods. The results showed that fungus B. bassiana was able to colonize soybean plants with a percentage of colonization reaching 6.67%. Colonization was only found in the stems of soybean plants in the seed immersion treatment with the susceptibility of B. bassiana fungus in density of 108 conidia / mL for 2 hours, colonization on the stem itself by 20%. Fungus density results from evaluation of 1.6 x 105 conidia / mL and conidial viability reached 87.4%. There were no deaths and changes in the population of A. glycine aphids. Direct pathogenicity testing has a significant effect on the treatment between observations of the second day. Initiation of B. bassiana fungi did not significantly affect plant height and number of leaf branches. This results conclude that B. bassiana may function as endophyte in soybean plants. However, its function in reduction of greenfly still need further researchKeywords: Biological control, Environmental pest management, Greenfly